Enhancement of periosteal bone formation by basic fibroblast‐derived growth factor containing polycystic kidney disease and collagen‐binding domains from Clostridium histolyticum collagenase. (18th March 2015) - Uchida, Kentaro; Matsushita, Osamu; Nishi, Nozomu; Inoue, Gen; Horikawa, Kyosuke; Takaso, Masashi
Abstract: Recombinant basic fibroblast growth factor (bFGF) is a potent mitogen for mesenchymal cells that accelerates bone union and repair when applied locally at defect sites. However, because bFGF diffuses rapidly from bone defect sites, repeated dosing is required for sustained therapeutic effect. We previously fused the collagen‐binding domain (CBD) and polycystic kidney disease (PKD) domain of Clostridium histolyticum class II collagenase (ColH) to bFGF and demonstrated that the fusion protein markedly enhances bone formation when loaded onto collagen materials used for grafting. However, systemic injection of a fusion protein consisting of parathyroid hormone (PTH) and a CBD was shown to accelerate bone formation in an osteoporosis model more rapidly than treatment with a PTH–PKD–CBD fusion protein. Here, we compared the biological properties of two collagen‐binding forms of bFGF, bFGF–CBD and bFGF–PKD–CBD. Both fusion proteins promoted the in vitro proliferation of periosteal mesenchymal cells, indicating that they had biological activity similar to that of native bFGF. In vivo periosteal bone formation assays in rat femurs showed that both bFGF–CBD and bFGF–PKD–CBD induced periosteal bone formation at higher rates than collagen sheet alone and bFGF. However, bFGF–PKD–CBD markedly enhanced bone formation and had higher collagen‐binding ability than bFGF–CBD in in vitro protein release assays. Taken together, these results suggest that the PKD domain increases the retention of bFGF at graft sites by enhancing collagen‐binding affinity. Therefore, bFGF–PKD–CBD–collagen composite appears to be a promising material for bone repair in the clinical setting. Copyright © 2015 John Wiley & Sons, Ltd.